Violation of Airspace Transit Rights by U.S. Military Aircraft in Indonesia's Archipelagic Sea Lanes - Khairuddin Alwi Fajar P; Suhaidi Suhaidi; Sutiarnoto Sutiarnoto (Hakamain: Journal of Sharia and Law Studies, 2025)
This study aims to examine the legal conformity of United States military aircraft operations within Indonesia’s Archipelagic Sea Lanes (ALKI) under the regime of archipelagic sea lanes passage as established by the 1982 United Nations Convention on the Law of the Sea (UNCLOS), and to determine the juridical criteria for identifying violations of airspace transit rights in this context. The research employs a normative juridical method based on statutory, conceptual, and case approaches, analyzing relevant UNCLOS provisions, Indonesia’s domestic regulations, doctrinal interpretations, and documented state practices related to military overflight. The findings indicate that while UNCLOS guarantees the right of continuous and expeditious overflight through designated archipelagic sea lanes, such rights are not absolute and must be exercised in normal mode, in good faith, and with due regard to the security interests of the archipelagic state. Ambiguities surrounding the interpretation of “normal mode” for military aircraft and the absence of detailed operational parameters create legal grey areas that may lead to differing perceptions between user states and Indonesia regarding alleged violations. The study concludes that clearer interpretative standards and cooperative mechanisms are necessary to prevent legal uncertainty and diplomatic friction. Academically, this research contributes to the development of international maritime and air law scholarship by bridging doctrinal analysis of UNCLOS with contemporary Indo-Pacific security practices, and by proposing a balanced legal framework that reconciles international navigation freedoms with the sovereign rights of archipelagic states.